Projeto experimental de publicidade e propaganda Grupo Cloow - Costa, Andressa Viegas da (2018)
This project aims to help the communication of the NGO Grupo Cloow, resident in the city of Getúlio Vargas, in order to win the confidence of the target audience, so that there is no fear of donating it. For this, it was used of research in primary data, going directly to the NGO and collecting a briefing, also was realized a field research, with structured questionnaire online, and applied to the target public. Afterwards, the organization and its context were outlined and later carried out a communication planning, in addition to the execution of the necessary parts to make it effective. Together, a day of action was carried out, making the members of this project have direct contact with the voluntary work carried out by the NGO. Afterwards, there is a report on the project, explaining the members' experience in the execution of the project, and finally, the final considerations, which point out the relevance of the project to the current NGO moment, stressing that the tactics proposed here do not solve instant the problem encountered, after all, win the trust of the target audience demand time. However, here are the first steps to be followed and tested, so that the next can be planned and put into practice, reaching the desired result: to be seen as a serious, transparent NGO that depends on the help of society to carry out your job.